2013
DOI: 10.3340/jkns.2013.54.6.496
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Menopause on Bone Fusion after the Single-Level Anterior Cervical Discectomy and Fusion

Abstract: ObjectiveTo evaluate the successful fusion rate in postmenopausal women with single-level anterior cervical discectomy and successful fusion (ACDF) and identify the significant factors related to bone successful fusion in pre- and postmenopausal women.MethodsFrom July 2004 to December 2010, 108 consecutive patients who underwent single-level ACDF were prospectively selected as candidates. Among these, the charts and radiological data of 39 women were reviewed retrospectively. These 39 women were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In studies by Lee et al 15) and Song et al 28) , however the VAS scores in the cage-with-plate fixation group were significantly better than those in the cage-only group in the one-level ACDF. This can be explained by an imbalance of the cervical lordotic curve resulting from cage subsidence 20 , 22) , or increased tension of the posterior cervical area due to pseudoarthrosis. Regarding the relationship between subsidence and clinical outcome, some studies report no correlation, but a study by Lee et al 16) reported that groups with high subsidence rates had poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In studies by Lee et al 15) and Song et al 28) , however the VAS scores in the cage-with-plate fixation group were significantly better than those in the cage-only group in the one-level ACDF. This can be explained by an imbalance of the cervical lordotic curve resulting from cage subsidence 20 , 22) , or increased tension of the posterior cervical area due to pseudoarthrosis. Regarding the relationship between subsidence and clinical outcome, some studies report no correlation, but a study by Lee et al 16) reported that groups with high subsidence rates had poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery is commonly used to treat the complaints of the patients with CSR, there are still many factors affecting the prognosis of these surgical procedures that should be evaluated. Some of known surgical prognostic factors that are frequently quoted include patient's psychiatric problem [ 26 ], failure to comply with a technically accurate surgery [ 2 , 6 ], and smoking status of the patient [ 27 ] but menopausal status [ 28 ], workman's compensation claims [ 29 ], and cage subsidence [ 30 ] seem to have no adverse effect on clinical outcome of ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Park et al, they evaluated the impact of menopause on bone fusion after single-level ACDF on 39 patients (11 in premenopausal and 28 in postmenopausal group) [ 28 ]. They could not find significant difference in the successful fusion rate or successful fusion type between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, nonsteroidal anti-inflammatory drug use, and menopause may also warrant the use of cervical plates due to increased rates of pseudarthrosis. Although a recent study suggested that postmenopausal women may not have a significantly increased risk of fusion failure compared to younger women [ 21 ], smoking remains to be one of the main predictors of unsuccessful fusion following spinal surgery [ 22 ].…”
Section: Reviewmentioning
confidence: 99%